Stimulating pyruvate dehydrogenase complex reduces itaconate levels and enhances TCA cycle anabolic bioenergetics in acutely inflamed monocytes. Issue 3 (2nd January 2020) - Zhu, Xuewei; Long, David; Zabalawi, Manal; Ingram, Brian; Yoza, Barbara K.; Stacpoole, Peter W.; McCall, Charles E.
Abstract: The pyruvate dehydrogenase complex (PDC)/pyruvate dehydrogenase kinase (PDK) axis directs the universal survival principles of immune resistance and tolerance in monocytes by controlling anabolic and catabolic energetics. Immune resistance shifts to immune tolerance during inflammatory shock syndromes when inactivation of PDC by increased PDK activity disrupts the tricarboxylic acid (TCA) cycle support of anabolic pathways. The transition from immune resistance to tolerance also diverts the TCA cycle from citrate-derived cis -aconitate to itaconate, a recently discovered catabolic mediator that separates the TCA cycle at isocitrate and succinate dehydrogenase (SDH). Itaconate inhibits succinate dehydrogenase and its anabolic role in mitochondrial ATP generation. We previously reported that inhibiting PDK in septic mice with dichloroacetate (DCA) increased TCA cycle activity, reversed septic shock, restored innate and adaptive immune and organ function, and increased survival. Here, using unbiased metabolomics in a monocyte culture model of severe acute inflammation that simulates sepsis reprogramming, we show that DCA-induced activation of PDC restored anabolic energetics in inflammatory monocytes while increasing TCA cycle intermediates, decreasing itaconate, and increasing amino acid anaplerotic catabolism of branched-chain amino acids (BCAAs). Our study provides new mechanistic insight that the DCA-stimulated PDC homeostat reconfigures the TCA cycle and promotes anabolic energetics in monocytes by reducing levels of the catabolic mediator itaconate. It further supports the theory that PDC is an energy sensing and signaling homeostat that restores metabolic and energy fitness during acute inflammation.